Current status of measles in the Republic of Korea: an overview of case-based and seroepidemiological surveillance scheme - Young June Choe; Geun-Ryang Bae (Korean Pediatric Society, 2012)
Following the Five Year Measles Elimination Program, measles has been declared eliminated from the Republic of Korea since 2006. However, there remain challenges related to the surveillance of measles in the postelimination phase. Even though the routine surveillance system has revealed a gradual decrease in the number of reported cases since 2002, 4 resurgences have occurred, notably due to outbreaks. Because vaccine-modified measles is becoming widespread due to high vaccination coverage, conducting laboratory confirmation in each case becomes important. Moreover, susceptible individuals with measles have been identified through seroprevalence studies. Lastly, the efforts to improve the timeliness of measles reporting have led to the establishment of an active laboratory-based surveillance network, which has shortened the interval between diagnosis and notification. In these circumstances, searching for more sensitive and effective surveillance measures is important for maintaining the elimination status and preventing future outbreaks of measles in Korea.